2023
DOI: 10.37074/jalt.2023.6.1.16
|View full text |Cite
|
Sign up to set email alerts
|

The role of online tourism education and its impact on student wellbeing during a ‘COVID-pause’

Abstract: The COVID-19 pandemic created an extremely challenging landscape for the tourism and hospitality industry, particularly in terms of the wellbeing of those employed in the sector. In mid-2020, in response to the pandemic, the University of Tasmania, in conjunction with the Tourism Industry Council of Tasmania, designed a fee-free Graduate Certificate of Tourism, Environmental and Cultural Heritage for Tasmanian residents employed in the tourism sector who were impacted by COVID-19. The course was designed to up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In comparison to traditional teaching and learning methods, modern methods that incorporate the use of technology, social media, and the internet are more attractive to students and have improved student performance (Sirbu et al, 2014). Hardy et al (2023) also observed that well-constructed online learning can contribute to the learners' wellbeing and foster a sense of connection in a learner community. eStudentMentors are senior learners who volunteer to guide level 1 (LG5001) and level 2 (LG5002) German learners, who learn German at a Common European Framework of Reference for Languages (CEFR) A1 Level, through a dedicated chat group in their learning journey (Common European Framework of Reference for Languages, 2023).…”
Section: Article Info Introductionmentioning
confidence: 91%
“…In comparison to traditional teaching and learning methods, modern methods that incorporate the use of technology, social media, and the internet are more attractive to students and have improved student performance (Sirbu et al, 2014). Hardy et al (2023) also observed that well-constructed online learning can contribute to the learners' wellbeing and foster a sense of connection in a learner community. eStudentMentors are senior learners who volunteer to guide level 1 (LG5001) and level 2 (LG5002) German learners, who learn German at a Common European Framework of Reference for Languages (CEFR) A1 Level, through a dedicated chat group in their learning journey (Common European Framework of Reference for Languages, 2023).…”
Section: Article Info Introductionmentioning
confidence: 91%